The Role of Geographic Information Systems (GIS) in Participatory Conservation of Heritage Areas - Hamid Salimi; Somayeh Fadaei Nezhad Bahramjerdi; Rana Tootoonchi (European Journal of Geography)
In contemporary heritage management, participatory approaches play a crucial role in identifying and safeguarding values for a diverse range of stakeholders. This inclusive methodology involves professionals, local communities, historians, conservationists, and policymakers in conservation efforts. Successfully addressing challenges in stakeholder engagement is crucial for promoting ownership and stewardship, thereby supporting sustainable conservation efforts. Various methods such as community workshops and collaborative mapping exercises have been adopted. Geographic Information Systems (GIS) have emerged as a valuable tool in facilitating stakeholder participation. This research explores the potential of GIS in participatory heritage conservation. It aims to present principles and considerations to outline the practical application of GIS in engaging communities for heritage conservation. By bridging traditional heritage management practices with contemporary participatory methods, the research aims to enhance inclusive, informed, and sustainable conservation efforts. On this basis, qualitative methods and logical argumentation are used to analyze research content, drawing on qualitative and quantitative data from previous studies. A conceptual model is presented through a literature review, followed by an evaluation of five case studies from Iran, The USA, Finland, Egypt, and Spain that have utilized GIS in participatory planning processes. The research highlights GIS's capability to capture diverse social groups' perspectives on heritage values and priorities using participatory mapping. This integration of community insights empowers stakeholders in decision-making processes, enhancing inclusivity in heritage management and supporting community-driven initiatives for urban heritage preservation.